The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1155/2015/341723
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Ovarian Cancer: Not OnlyBRCA1 and 2 Genes

Abstract: More than one-fifth of ovarian tumors have hereditary susceptibility and, in about 65–85% of these cases, the genetic abnormality is a germline mutation in BRCA genes. Nevertheless, several other suppressor genes and oncogenes have been associated with hereditary ovarian cancers, including the mismatch repair (MMR) genes in Lynch syndrome, the tumor suppressor gene, TP53, in the Li-Fraumeni syndrome, and several other genes involved in the double-strand breaks repair system, such as CHEK2, RAD51, BRIP1, and PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
118
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(143 citation statements)
references
References 96 publications
3
118
1
6
Order By: Relevance
“…Early examination should be performed in individuals with a family history of malignancy. Thus, proactive steps can be taken for early detection, timely treatment, and improved prognosis in patients with ovarian cancer [22]. Decreases in body weight and BMI were observed in patients in the present study.…”
Section: Discussionsupporting
confidence: 46%
“…Early examination should be performed in individuals with a family history of malignancy. Thus, proactive steps can be taken for early detection, timely treatment, and improved prognosis in patients with ovarian cancer [22]. Decreases in body weight and BMI were observed in patients in the present study.…”
Section: Discussionsupporting
confidence: 46%
“…In addition, domestic and foreign researchers also found that gene polymorphism of Rad51 recognized as the risk factor of CRC carcinogenesis. At present, more studies are focusing on the 135G/C single nucleotide polymorphism of Rad51 gene, the allelic variation is regarded as a susceptible factor for CRC, but the exact mechanism is not yet clear, which may be related to the presence of a BRCA2 mutation [19]. In contrast, researches on the correlation between Rad51 and tumor metastasis are still insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The MMR system works to remove single-strand breaks from DNA by recognizing and correcting short insertions and deletions and single base pair mismatches. When these MMR genes are mutated areas of sequence repeats, microsatellites, can change in size which causes frameshift mutations and DNA instability (31). The overall lifetime risk of ovarian cancer for women with Lynch syndrome is estimated at 8-12% (30-32).…”
Section: Defining the Patient At High Risk Of Ovarian Cancermentioning
confidence: 99%
“…Using this technology additional inherited genes implicated in ovarian cancer have been identified (11, 14, 24, 31, 40). Panel testing among a high risk population, will identify pathogenic mutations in moderate or high penetrance genes (other than BRCA1/2 ) in 3.8% of women (41).…”
Section: Defining the Patient At High Risk Of Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation